Three new species of Neofidelia (Hymenoptera: Apoidea: Megachilidae) from Northern Chile - Dumesh, Sheila; Packer, Laurence (Zootaxa, 2013)
Neofidelia apacheta Dumesh and Packer, sp. nov., N. camanchaca Dumesh and Packer, sp. nov., and N. submersa Dumesh and Packer, sp. nov. are described from northern Chile. Neofidelia apacheta is known from large numbers of specimens and localities at moderately high elevation (1600–3200m). Neofidelia camanchaca is only known from the ho-lotype male. Neofidelia submersa is known from the holotype male and a pair of paratypes in poor condition, all from a coastal fog oasis. Comparisons are made with the two previously described species of the genus. The collection of N. apa-cheta from so far north in Chile suggests that Neofidelia is likely to be found in southern Peru. A key for the five species of the genus is provided.